1992
DOI: 10.5465/ambpp.1992.4976750
|View full text |Cite
|
Sign up to set email alerts
|

Political Influence Behavior and Career Success.

Abstract: In a recent review of the literature on politics and influence behavior in personnel/human resource management, noted that no studies had directly investigated the relationship between influence behavior and overall career success. In the present study the effect of political influence behavior on career success was investigated. Drawing from past research on influence behavior and relevant theory from social psychology, the effect of political influence behavior on career success was hypothesized to depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…Swiss, 1996). Past research also found that job-focused, self-promoting tactics result in lower career success, but supervisor-focused, ingratiating tactics have positive links (Judge and Bretz, 1994). It is possible that the scale used in this study comprised items which are more job-focused than supervisor-focused.…”
Section: Discussionmentioning
confidence: 83%
“…Swiss, 1996). Past research also found that job-focused, self-promoting tactics result in lower career success, but supervisor-focused, ingratiating tactics have positive links (Judge and Bretz, 1994). It is possible that the scale used in this study comprised items which are more job-focused than supervisor-focused.…”
Section: Discussionmentioning
confidence: 83%
“…There has been some research which has looked at levels of satisfaction among professional women, but relatively little is known about how satisfied professional women are with their careers (Auster, 2001), or how satisfied they are more generally (Hofstede et al , 2004). Dyke and Murphy (2006) compared definitions of success between successful men and women, who had notable achievements, and related these to satisfaction, noting that some authors (Judge and Bretz, 1994; Judge et al , 1995; Nabi, 2001) have used satisfaction with job and career progress as measures of subjective success. They found that balance was more important to women, and material success more important to men.…”
mentioning
confidence: 99%
“…This means tenure is often used as a surrogate for managerial skills[44] with longer tenure being associated with greater managerial skills. Some studies have found a positive relationship between tenure in a firm and career attainment for managers[33, 38, 45, 46, 47].…”
Section: Hypothesesmentioning
confidence: 99%